Re-planning of Concrete Structures in the Ngoro Dormitory Project in Surabaya - Rumbyarso, Yonas Prima Arga (Journal of Applied Science, Engineering, Technology, and Education, 2023)
The current trend of building construction is using steel frames and reinforced concrete frames. The construction design concept is based on strength limit analysis (ultimate strength) which has sufficient ductility to absorb earthquake energy according to applicable regulations. In addition to this, it is also necessary to consider the economic aspect. All of these structural considerations will influence planning alternatives, such as column layout, beam length, and span. Dormitori Ngoro Surabaya is one of the low-rise buildings that will be redesigned to comply with SNI 2847:2013. This research is expected to answer the need for earthquake-resistant building construction using the ETABS program and according to SNI 2847:2013 standards. In this study the method used with the concept of Flowcharts in order to facilitate the research stage. As for this study, it produced a maximum moment of 137.58 KNm with the use of beam dimensions of 40 x 75 cm, using 8D16 top main reinforcement and 3D16 bottom main reinforcement with stirrups D10-200 in the support area and D10-100 in the field area. Whereas the ratio of beam reinforcement based on manual calculations is 0.24% and the ETABS results are 0.22%.